PENGARUH THE DAY OF WEEEK EFFECT, WEEK FOUR EFFECT DAN ROGALSKY EFFECT TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS KOMPAS 100 - ILHAMI, ADITYA PRATIWI ILHAMI B1022141013 (Jurnal Manajemen Update, 2018)
ABSTRACTThe purpose of this research is to examine the day of week, week four effect and Rogalsky effect toward stock return on Kompas 100 company. The sample is selected using Purposive Sampling Technique. The sample consist are sixty five active stock on Kompas 100 company during January 2013 trough December 2017. The statistic methods which are used to test hypotheses are multiple linear regression, One Sample T-test and Independent T-test. The result show that there are a day of week effect, week four effect and Rogalsky effect exist on Kompas 100 company.Keywords : The Day of Week Effect, Week Four Effect, Rogalsky Effect, Stock Return, Kompas 100 Index. DAFTAR PUSTAKAAmbarwati, Sri Dwi Ari. (2009). Pengujian Week Four, Monday, Friday dan Earning Management Effect terhadap Return Saham. Jurnal Keuangan dan Perbankan, Vol.13, No.1: 1-14.Ardinan, Haikel. (2014). Pengujian Monday Effect pada Bursa Efek Indonesia dan Bursa Efek Singapura. Journal of Business and Banking, Volume 4, No 1: 81-90.Cahyaningdyah, Dwi. (2005). Analisis Pengaruh Hari Perdagangan terhadap Return Saham: Pengujian Week Four Effect dan Rogalski Effect di Bursa Efek Jakarta. Jurnal Ekonomi dan Bisnis Indonesia. Vol. 20, No.2: 175-186Darmadji, T., dan Hendi, F. (2001). Pasar Modal Indonesia. Edisi pertama. Jakarta: Salemba Empat.Fama, E.F,. (1970). Efficient Capital Markets: A Review of Theory and Empirical Work. Journal of Finance 25: 383 – 417. Dalam Jogiyanto, Hartono. (2014). Teori Portofolio dan Analisis Investasi.  Edisi Ketujuh. Yogyakarta: BPFE-Yogyakarta.French, K. (1980). Stock Returns and the Weekend Effect. Journal of Financial Economics. Vol. 8. pp 55-69.Gibbons, M. and Hess, P. (1981). Day of the Week Effects and Asset Returns.  Journal of Business. Vol. 54. pp 579-596.Gumanti, Tatang Ary. (2011). Manajemen Investasi Konsep, Teori dan Aplikasi. Edisi Pertama. Mitra Wacana Media.Iramani dan A Mahdi. (2006). Studi Tentang Pengaruh Hari Perdagangan Terhadap Return Saham pada BEJ. Journal akutansi dan keuangan, Vol.8, No.2: 63-70.Jones, Charles. (2007). Investments: Analysis and Management. Edisi Kesepuluh. United States: North Carolina State University.Rogalsky, Richard J,. (1984). A New Finding Regarding Day of The Week Returns Over Trading and Non Trading Periods. Journal of Finance. 39 (5): 1603-1614Saraswati, Y.R., Setiorini, C., & Cornelia, D.A. (2015). Pengaruh The Day of the Week Effect, Week Four Effect dan Rogalsky Effect terhadap Return Saham LQ45 di Bursa Efek Indonesia. Jurnal Riset Akutansi dan Perpajakan :JRAP. Vol.2, No.1: 43-54, ISNN 2339-1545.Satoto, H. Shinta. (2015). Analisis Fenomena Day of the Week Effect : Pengujian Monday Effect, Week Four Effect dan Rogalsky Effect (Studi Empiris pada Perusahaan LQ45 di BEI). Jurnal Manajemen. Vol.10, No.2Tandelilin, Eduardus. (2010). Portofolio dan Investasi. Kanisius: Yogyakarta.Wang, KY. And Li, J Erikson. (1997). A New Look At The Monday Effect. Journal of Finance. LII (5): 2171-2186. Dalam Ardinan, Haikel. (2014). Pengujian Monday Effect pada Bursa Efek Indonesia dan Bursa Efek Singapura. Journal of Business and Banking, Volume 4, No 1: 81-90.Werastuti, Sri, D.N,. (2012). Anomali Pasar pada Return Saham : The Day of The Week Effect, Week Four Effect, Rogalsky Effect, dan January Effect. Jurnal Ilmiah Akuntansi dan Humanika JINAH. vol. 2, No.1, 2012. Dalam Saraswati, Y.R., Setiorini, C., & Cornelia, D.A. (2015). Pengaruh The Day of the Week Effect, Week Four Effect dan Rogalsky Effect terhadap Return Saham LQ45 di Bursa Efek Indonesia. Jurnal Riset Akutansi dan Perpajakan :JRAP. Vol.2, No.1: 43-54, ISNN 2339-1545.